Modeling of Electric Fields in Individual Imaging Atlas for Capsular Threshold Prediction of Deep Brain Stimulation in Parkinson's Disease: A Pilot Study - Béreau, Matthieu; Kibleur, Astrid; Bouthour, Walid; Tomkova Chaoui, Emilie; Maling, Nicholas; Nguyen, T. A. Khoa; Momjian, Shahan; Vargas Gomez, Maria Isabel; Zacharia, André; Bally, Julien F.; Fleury, Vanessa; Tatu, Laurent; et al. (Frontiers in Neurology, 2020)
Background: Modeling of Deep Brain Stimulation electric fields and anatomy-based software might improve postoperative management of patients with Parkinson’s disease (PD) who have benefitted from subthalamic nucleus Deep Brain Stimulation (STN-DBS). Objective: We compared clinical and software-guided determination of the thresholds for current diffusion to the pyramidal tract, the most frequent limiting side effect in postoperative management of STN-DBS PD patients. Methods: We assessed monopolar reviews in sixteen consecutive STN-DBS PD patients and retrospectively compared clinical capsular thresholds, which had been assessed according to standard clinical practice, to those predicted by volume of tissue activated (VTA) model software. All the modeling steps were performed blinded from patients’ clinical evaluations. Results: At the group level, we found a significant correlation (p=0.0001) when performing statistical analysis on the z-scored capsular thresholds, but with a low regression coefficient (r=0.2445). When considering intra-patient analysis, we found significant correlations (p<0.05) between capsular threshold as modeled with the software and capsular threshold as determined clinically in five patients (31.2%). Conclusions: In this pilot study, the VTA model software was of limited assistance in identifying capsular thresholds for the whole cohort due to a large inter-patient variability. Clinical testing remains the gold standard in selecting stimulation parameters for STN-DBS in PD.